PENGUATAN KESEHATAN REPRODUKSI REMAJA - Srimiyati Srimiyati; Bangun Dwi Hardika; Aprilia Susanty; Vincencius Surani; Nyoman Anda Resta (Jurnal Abdimas Musi Charitas, 2018)
Adolescence (11-20 years) is a special and important period, because it is the period of maturation of human reproductive organs (Widyastuti, 2009). Adolescence is in a very sensitive situation to the effect of new values, especially for those who have no power of deterrence. The most prominent issues among adolescents related to reproductive health today, such as reproductive health, early marriage, pregnancy out of wedlock and abortion to make adolescence become non-character (Caesarina, 2009). This activity was conducted on Tuesday, January 9, 2018 at SMA Sint Carolus Bengkulu. Through this activity, participants are expected to have good knowledge and attitude about reproduction health. The methods used are lectures, interactive discussions and individual consultations. Of the 51 participants who attended the event, it was found that after the activity, the majority of them stated that this activity was interesting, their understanding and attitude about reproductive health was good.